Information-seeking behaviour of grade R practitioners in the Ekurhuleni Metropolitan Municipality - Madumo, Kepi David (Library and Information Studies Centre (LISC), 2017)
In this study, the information-seeking behaviour of Grade R practitioners in the Ekurhuleni Metropolitan Municipality in Gauteng Province, South Africa was investigated. The investigation included determining information needs, information sources often consulted, actions and strategies used when seeking information and challenges faced by these practitioners when seeking information. Early Child Development practitioners need information to increase their knowledge for optimum performance of their duties. Literature points to a possibility that if the Grade R practitioners can have access to relevant, accurate and timeous information and gain essential information retrieval skills, they might develop capacity for innovation, creativity and ultimately improve their teaching. Currently, Ekurhuleni Metropolitan Municipality libraries do not have any service dedicated to Early Child Development practitioners, yet Early Child Development is a national government priority stipulated in the National Development Plan. In the interest of developing relevant information services for Early Child Development practitioners, as Early Child Development is one of the national priorities, the researcher needed to ascertain their information needs and information-seeking behaviour. Using Leckie, Pettigrew and Sylvain's General Model of the Information Seeking of Professionals as the theoretical framework; and situated within interpretivist paradigm, the study took a qualitative approach to collect data through group discussions and an interview with a key informant. The results are based on seven focus group discussions with the practitioners from public schools, independent schools and community-based Early Child Development centres. These show that the practitioners' most popular information sources are Google, social media, especially Pinterest, and their colleagues. The major barriers to information access are time restraints and language. The nature of information needed to perform their tasks ranges from curriculum-related information, various child development oriented topics, legislation and information related to their personal and professional development. A few participants who claimed to use libraries indicated that they use neither the library catalogue nor the online databases in the library. In fact, they preferred to browse the shelves to find books and had never asked the library staff for any assistance. The majority of the participants do not use libraries, even though they appreciated the importance of information and library services in providing critical information for execution of their duties. To satisfy the demand for information, it is recommended that the Ekurhuleni Metropolitan Municipality libraries and the Gauteng Department of Education school libraries should consider a coordinated and accessible library and information service that supports Early Child Development practitioners. The plans and design of library and information service in the Ekurhuleni Metropolitan Municipality should accommodate the information needs expressed by the Grade R practitioners. Keywords: Early childhood practitioner, Grade R, pre-preparatory, pre-school, pre-primary, information-seeking behaviour, Ekurhuleni Metropolitan Municipality, early childhood development, library and information service(s).